2021
DOI: 10.1186/s13584-021-00443-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between hallway boarding in internal wards, readmission and mortality rates: a comparative, retrospective analysis, following a policy change

Abstract: Background Emergency department overcrowding is associated with adverse clinical outcomes and poor patients and staff experience. Full capacity protocols enabling hallway boarding in internal wards are instituted to relieve emergency room overcrowding. The effect of hallway boarding on the clinical outcomes of all inpatients in the internal wards has not been studied. Early in 2016, a decision to enable hallway boarding in the internal wing in our medical center came into effect, comprising an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 28 Surveys elsewhere that explored patients perceptions and experiences suggest that they overwhelmingly prefer inpatient hallway boarding to ED boarding. 28 , 29 , 30 Shoham et al 31 found that inpatient hallway boarding in a hospital in Jerusalem lowered inpatient mortality (OR 0.76, [CI, 0.65 to 0.90]) but increased the 30-day readmission rate (OR, 1.18 [CI, 1.00 to 1.40]). Nursing perceptions differed depending on where they work, with unsurprisingly ward nurses being opposed to inpatient hallway boarding and ED or ex-ED nurses supporting it.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Surveys elsewhere that explored patients perceptions and experiences suggest that they overwhelmingly prefer inpatient hallway boarding to ED boarding. 28 , 29 , 30 Shoham et al 31 found that inpatient hallway boarding in a hospital in Jerusalem lowered inpatient mortality (OR 0.76, [CI, 0.65 to 0.90]) but increased the 30-day readmission rate (OR, 1.18 [CI, 1.00 to 1.40]). Nursing perceptions differed depending on where they work, with unsurprisingly ward nurses being opposed to inpatient hallway boarding and ED or ex-ED nurses supporting it.…”
Section: Discussionmentioning
confidence: 99%
“…While it is somewhat lower than the 4-7 per 1,000 birth prevalence previously reported in two small studies 39,47 and in one similar-scale study 48 in Israel, the findings highlight the importance of ongoing large-scale screening in defining the true population prevalence of cCMV. In this regard, it is noteworthy that the population of Jerusalem uniquely consists of segregated communities characterized by different maternal fertility and seroprevalence rates 49 . As cCMV prevalence varies considerably according to ethnic grouping, ethnicity and maternal seroprevalence 1,4,9,12,50 , it will be important to further assess the prevalence of cCMV in distinct subpopulations.…”
Section: Articlementioning
confidence: 99%